Primary and acquired multidrug-resistant tuberculosis: Predictive factors for unfavorable treatment outcomes in Rio de Janeiro, 2000–2016 - Bhering, Marcela (Rev Panam Salud Publica, 2020)
OBJECTIVE: To identify clinical and demographic factors associated with unfavorable treatment outcomes in patients with primary and acquired multidrug-resistant tuberculosis (MDR-TB) in Rio de Janeiro State. METHODS: Retrospective cohort study using data on 2 269 MDR-TB cases in 2000–2016. Factors associated with unsuccessful, loss to follow-up, and death outcomes in patients with primary and acquired resistance were investigated with bivariate and multivariate regression. RESULTS: Primary resistance was 14.7% among MDR-TB cases. The unfavorable outcomes proportion was 30.3% in the primary resistance group and 46.7% in the acquired resistance group. There were significant differences in demographic and clinical characteristics between the two groups. Proportionally, the group with primary resistance had more cases among women (46.4% vs. 33.5% in the acquired resistance group), Caucasians (47.3% and 34%), and those with ≥8 years of schooling (37.7% and 27.4%). Extensively drug-resistant TB patients had 12.2-fold higher odds of unsuccessful outcome than MDR-TB patients, and comorbidities had 2-fold higher odds in the primary resistance group. Extensively drug-resistant TB had 5.43-fold higher odds in the acquired MDR-TB group. Bilateral disease and <8 years of schooling were associated with unsuccessful outcome in both groups. Being an inmate had 8-fold higher odds of loss to follow-up in the primary resistance group. Culture conversion by the sixth month was a protective factor for all outcomes. CONCLUSIONS: Primary resistance cases of MDR-TB constitute a different transmission reservoir, which is related to other chronic diseases associated with higher acquisition of TB. The poor results observed in Rio de Janeiro State can contribute to increasing the transmission of primary MDR-TB, thus favoring drug resistance.